2007
DOI: 10.1103/physrevb.76.052510
|View full text |Cite
|
Sign up to set email alerts
|

Angle-dependent magnetoresistance oscillations due to magnetic breakdown orbits

Abstract: We present experimental evidence for a hitherto unconfirmed type of angle-dependent magnetoresistance oscillation caused by magnetic breakdown. The effect was observed in the organic superconductor κ-(BEDT-TTF)2Cu(NCS)2 using hydrostatic pressures of up to 9.8 kbar and magnetic fields of up to 33 T. In addition, we show that similar oscillations are revealed in ambient pressure measurements, provided that the Shubnikov-de Haas oscillations are suppressed either by elevated temperatures or filtering of the data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…Superconducting crystals include large solvent crystals, and the superconducting transition temperature ZORINA et al increases with the solvent molecule size. These crystals exhibit Shubnikov-de Haas magnetic oscillations at one or two frequencies [20][21][22][23]. Superconductivity is often preceded by a complex temperature dependence of the electrical resistance with a broad minimum in the range 40-150 K in various phases [21,22].…”
Section: H 3 O[fe III (C 2 O 4 )mentioning
confidence: 99%
See 1 more Smart Citation
“…Superconducting crystals include large solvent crystals, and the superconducting transition temperature ZORINA et al increases with the solvent molecule size. These crystals exhibit Shubnikov-de Haas magnetic oscillations at one or two frequencies [20][21][22][23]. Superconductivity is often preceded by a complex temperature dependence of the electrical resistance with a broad minimum in the range 40-150 K in various phases [21,22].…”
Section: H 3 O[fe III (C 2 O 4 )mentioning
confidence: 99%
“…These crystals exhibit Shubnikov-de Haas magnetic oscillations at one or two frequencies [20][21][22][23]. Superconductivity is often preceded by a complex temperature dependence of the electrical resistance with a broad minimum in the range 40-150 K in various phases [21,22]. Below this temperature, the resistance increases slowly, which is related to partial charge localization [22], and the increase in the resistance is then changed by a sharp decrease in a superconducting state.…”
Section: H 3 O[fe III (C 2 O 4 )mentioning
confidence: 99%
“…[8][9][10][11][12][13] and are observed in a number of organic conductors, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] which possess Q1D parts in their Fermi surfaces ͑FSs͒. Note that, instead of maxima of resistivity due to electron-electron scattering, predicted in Ref.…”
Section: Introductionmentioning
confidence: 95%
“…15,16. It is expected that this approach to summing all the contributions to the MB network model will open up new avenues in research on low-dimensional metals.…”
Section: (B)-(d) As Well As Many Other Intermediate Possibilities Inmentioning
confidence: 99%
“…In this Letter we describe a novel strategy to efficiently compute AMROs in a model system exhibiting MB which includes explicitly all these processes and we use it to show how different features in real data may arise. Our results are discussed in the context of recent experimental work [15] on the crystalline organic metal κ-(BEDT-TTF) 2 Cu(NCS) 2 which demonstrated that, at high field, breakdown AMROs (BAMROs) could be identified in exarXiv:0709.2827v1 [cond-mat.str-el] …”
mentioning
confidence: 99%